Reaffirming the Golden Hour: Optimizing Door-to-Balloon Time for STEMI Patients in Pakistan - Ahmad Fawad; Saadia Ilyas; Hamid Mahmood (Pakistan Heart Journal, 2025)
The study by Hussain et al. [1] offers important insight into a critical determinant of STEMI outcomes: door-to-balloon (D2B) time. This prospective single-center analysis reinforces the established global consensus that rapid reperfusion significantly improves outcomes in patients undergoing primary percutaneous coronary intervention (PCI). In doing so, it situates this universal principle within the distinct challenges of Pakistan’s healthcare system, where data on STEMI care processes remain relatively limited. Numerous registries and randomized clinical trials have consistently demonstrated that minimizing ischemic time reduces infarct size, preserves left ventricular function, and lowers mortality rates [2,3]. Echoing this evidence, Hussain et al. report significantly lower in-hospital mortality (3.3%) and major adverse cardiac events (6.7%) in patients with D2B times under 60 minutes compared to those whose treatment exceeded 90 minutes (20% and 30%, respectively). These findings affirm that faster reperfusion is not only desirable but lifesaving. What distinguishes this study is its contextual relevance. While international benchmarks have long set the standard for STEMI care, translating these into low- and middle-income country (LMIC) settings is often impeded by infrastructure limitations. Prior observations from institutions such as the Peshawar Institute of Cardiology and the National Institute of Cardiovascular Diseases (NICVD) have highlighted systemic inefficiencies including delayed triage, underdeveloped emergency medical services (EMS), and lack of coordinated STEMI networks [4,5]. Hussain et al. underscore these familiar obstacles but also demonstrate that improvements in D2B performance are achievable even within existing hospital frameworks [1]. An especially meaningful contribution of this study is its stratified analysis by comorbidity status. Patients with hypertension, diabetes, and hyperlipidemia experienced longer D2B times, suggesting that complex clinical profiles may contribute to treatment delays, potentially through diagnostic ambiguity or procedural hesitations [6]. This highlights the urgent need for streamlined, risk-adapted care pathways—an approach consistent with the ethos of precision medicine. The study also prompts renewed attention to pre-hospital delays, which are not captured in D2B metrics but critically influence total ischemic time. While the investigation begins at the point of hospital arrival, it is well recognized that patient hesitation, transport delays, and lack of EMS coordination erode valuable treatment time [7]. International experience demonstrates that integrating EMS systems, tele-ECG triage, and regional STEMI networks can dramatically reduce total ischemic time and should be prioritized in Pakistan [8]. These findings support the call for broader structural and policy reforms. High-volume tertiary facilities—such as Hayatabad Medical Complex—should consider implementing rapid triage algorithms, 24/7 catheterization lab teams, and real-time D2B performance monitoring systems [8]. At a national level, the establishment of a standardized STEMI registry, akin to the NCDR (USA) or MINAP (UK), could play a transformative role in benchmarking quality and harmonizing care [9,10]. In this regard, the recent launch of the Cardiac Registry of Pakistan (CROP) represents a pivotal advancement. However, widespread adoption and consistent reporting across all PCI-performing centers are essential for its impact to be realized. While the study is strengthened by its prospective design and focus on clinically meaningful endpoints, certain limitations must be acknowledged. Being a single-center study, generalizability is restricted. Retrospective data extraction also introduces potential documentation bias. Moreover, the exclusion of total ischemic time and lack of long-term follow-up limit the assessment of sustained outcomes. Nevertheless, the study provides clear, focused evidence to support the use of D2B time as a key quality metric in the care of STEMI patients in Pakistan. Hussain et al. offer compelling, context-specific evidence that underscores the critical importance of reducing D2B time to improve survival and reduce adverse outcomes in STEMI patients [1]. Their findings support the international guideline-recommended target of